(untitled) (Vietnam Journal of Community Medicine, 2026)
1.Purpose: This study aimed to describe the morphology, dimensions, and footprint sites of the anterior inferior tibiofibular ligament (AITFL) and the posterior inferior tibiofibular ligament (PITFL) in adult Vietnamese cadavers. 2.Methods: A cross-sectional descriptive study was conducted on 50 ankle joints from 25 adult Vietnamese formalin-fixed cadavers. Standardized dissection techniques were used to identify ligament morphology, number of bands, dimensions, and footprint areas of the AITFL and the PITFL on the tibia and fibula. Statistical analysis was performed using STATA version 15.0. 3.Results: The AITFL was classified into three types (one, two and three band configurations), with the single band type being the most prevalent, whereas the superficial the posterior inferior tibiofibular ligament (sPITFL) was observed only as one or two band structures. The mean length, width, and thickness of the AITFL were 17.2 ± 4.4 mm, 13.9 ± 4.3 mm, and 2.1 ± 0.9 mm, respectively with mean footprint areas of 79.3 ± 26.2 mm² on the fibula and 78.5 ± 41.1 mm² on the tibia. The PITFL comprises a superficial band that is wider and thinner, and a deep band that is narrower, thicker, and longer; the footprint area of the superficial band is larger than that of the deep band on both the tibia and the fibula. 4.Conclusion: The AITFL and the PITFL in adult Vietnamese individuals exhibit morphological features and footprint locations consistent with those reported in international studies; however, certain differences are present in band architecture and footprint areas.